Monte Carlo simulations of the electron: gas interactions in the KATRIN experiment - Kellerer, Jonas; Spanier, Felix (Journal of Instrumentation, 2022)
At the KATRIN experiment, the electron antineutrino mass is inferred from the shape of the β-decay spectrum of tritium. Important systematic effects in the Windowless Gaseous Tritium Source (WGTS) of the experiment include the energy loss by electron scattering, and the extended starting potential. In the WGTS, primary high-energy electrons from β-decay produce an extended secondary spectrum of electrons through various atomic and molecular processes including ionization, recombination, cluster formation and scattering. In addition to providing data essential to the simulation of energy loss processes, the electron spectrum also provides information important in the simulation of plasma processes. These simulations will then provide an insight on the starting potential. Here, a Monte Carlo approach is used to model the electron spectrum in the source for a given magnetic and electric field configuration. The spectrum is evaluated at different positions within the WGTS, which allows for a direct analysis of the spectrum close to the rear wall and detector end of the experiment. Alongside electrons, also ions are tracked by the simulation, resulting in a full description of the currents in the source.
Gesehen am 17.08.2022